The Role of Zoom Cloud Meeting as Learning Online Medium in Pandemic - Rianita, Dian; Muzdalifah, Indah (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Before the arrival of the Covid 19 virus epidemic, the government actually launched the industry 4.0 and 5.0 revolutions, including in the field of education where the use of technology as a medium or instrument in learning can be maximized to use. However, most of teacher and students were not able to conduct yet. When this epidemic comes, it can’t help using technology in the field of education ready or not. The government’s policy to execute large-scale social restrictions or PSBB to prevent the transmission of the epidemic has made the implementation of the teaching and learning process online starting from elementary level to university. However, every change certainly causes pros and cons. There are both positive and negative sides to online learning. The positive side can make it easier and more efficient for face-to-face learning to be done from home anytime and anywhere. Meanwhile, the problems that arise include a lack of understanding in the use of technology, inadequate internet network facilities and many more effects as a result of this online learning. Therefore, this article discusses the phenomena that occur around education caused by the impact of the outbreak in the middle of the Covid 19 pandemic.